Recent new insights into the role of SNARE and associated proteins in insulin granule exocytosis. (September 2017) - Gaisano, Herbert Y.
Abstract : Initial work on the exocytotic machinery of predocked insulin secretory granules (SGs) in pancreatic β‐cells mimicked the SNARE hypothesis work in neurons, which includes SM/SNARE complex and associated priming proteins, fusion clamps and Ca 2+ sensors. However, β‐cell SGs, unlike neuronal synaptic vesicles, exhibit a biphasic secretory response that requires additional distinct features in exocytosis including newcomer SGs that undergo minimal docking time at the plasma membrane (PM) before fusion and multi‐SG (compound) fusion. These exocytotic events are mediated by Munc18/SNARE complexes distinct from that which mediates predocked SG fusion. We review some recent insights in SNARE complex assembly and the promiscuity in SM/SNARE complex formation, whereby both contribute to conferring different insulin SG fusion kinetics. Some SNARE and associated proteins play non‐fusion roles, including tethering SGs to Ca 2+ channels, SG recruitment from cell interior to PM, and inhibitory SNAREs that block the action of profusion SNAREs. We discuss new insights into how sub‐PM cytoskeletal mesh gates SG access to the PM and the targeting of SG exocytosis to PM domains in functionally polarized β‐cells within intact islets. These recent developments have major implications on devising clever SNARE replacement therapies that could restore the deficient insulin secretion in diabetic islet β‐cells.